The relative ability of different front-of-pack labels to assist consumers discriminate between healthy, moderately healthy, and unhealthy foods - Talati, Zenobia; Pettigrew, Simone; Ball, K.; Hughes, C.; Kelly, B.; Neal, B.; Dixon, H. (Pergamon, 2017)
The degree to which different front-of-pack labels (FoPLs) can assist consumers to make healthy choices seems to depend on the extent to which the FoPLs provide an interpretation of the nutrition information presented. The aim of this study was to assess the effectiveness of three FoPLs that vary by interpretive content in allowing consumers to discriminate between products of varying healthiness. Australian consumers (n = 2058) rated the perceived healthiness of mock food pack images that varied according to: nutritional profile (healthy, moderately healthy, unhealthy); FoPL (Daily Intake Guide (DIG), Multiple Traffic Lights (MTL), Health Star Rating (HSR), or control); and food type (cookies, cornflakes, pizza, yoghurt). Respondents were most accurate at differentiating unhealthy products from healthy (p < 0.001) and moderately healthy products (p = 0.015) when the HSR appeared on packs. The MTL was marginally (p = 0.052) effective at helping respondents distinguish between healthy and unhealthy products. When the DIG or no FoPL was used, however, respondents were unable to discriminate between a healthy and an unhealthy nutritional profile. Findings indicate that the HSR is more effective than other commonly used FoPLs in assisting consumers to accurately evaluate the healthiness of food products.